PENERAPAN JALUR SEPEDA DI JALAN SOEKARNO HATTA SEBAGAI UPAYA MENDORONG TRANSPORTASI RAMAH LINGKUNGAN DI KOTA MALANG - Martini Candy Angela; Rifky Aldila Primasworo; Pamela Dinar Rahma (Journal Innovation of Civil Engineering (JICE), 2026)
Soekarno Hatta Street is one of the main thoroughfares in the city of Malang, characterized by high levels of activity and heavy traffic, which contribute to congestion, reduced safety, and environmental degradation. The implementation of dedicated bike lanes is seen as a way to promote eco-friendly transportation while improving safety and comfort for non-motorized road users. The methods employed in this study include field observations, interviews, and questionnaires administered to the public and road users. Public perception analysis was conducted using the Importance Performance Analysis (IPA) method, which was used to understand the perceptions of the community and road users regarding the planned implementation of bicycle lanes on Soekarno-Hatta Road, while the technical assessment referred to the Guidelines for Designing Bicycle Facilities (05/SE/Db/2021). The results indicate that the road corridor has considerable potential for implementation as a bicycle lane; however, it still faces several obstacles, such as illegal parking and a lack of supporting facilities. Recommended strategies for implementing bicycle lanes include road space planning, the provision of markings and physical separators, improvements to lane surface quality, and integration with activity centers. The implementation of these strategies is expected to enhance safety, comfort, and public interest in using bicycles as a daily mode of transportation. Keywords: Bicycle Lanes; Sustainable Transportation; Public Perception; IPA Analysis.